Farinha pouca, primeiro meu pirão: trajetória da constituição da subjetividade do trabalhador gestor - Patricia Aparecida Abreu Moreira (2016)
The new forms of administration do, which leaves aside the rigid and formal structures work based in the Taylor logic for admission considered a model "flexible"; They include mechanisms increasingly sophisticated control of the workforce (FARIA, 2007). The study of the relationship between objectivity and subjectivity in labor relations instigates them before the manager's condition: he is the mediator of organizational contradictions, experiences the contradictions of work and organizational discourse in everyday life, and also is a member of the working class, despite of often find it difficult to see as such. To find answers to this problem is made possible investigating managers who work in the financial sector. The research developed was moved by questioning the form of constitution of the subjectivity of managers. To enable the formation of empirical corpus that supports the analytical generalizations, systematic observations will be used, document analysis and the life story of managers. To allow the approach, documents produced by the financial institution and was carried out systematic observation of the routine of managers were analyzed. In addition, managers were interviewed and used the technique to analyze the history of life. The analysis of the phenomenon made it possible to reflect on the construction of a subjectivity guided by the minimal presence of bonds of trust, solidarity and class identity. Changes in forms of management in the last twenty years in business and experienced by managers interviewed demonstrate that before there was a sense of production friendships in the workplace, today's fierce competition, the automation of decisions in the way of doing the job and performance evaluation system for "progression" in his career, pushed the construction of positive emotional bonds in the workplace. The objectivity of the work process is producing a social being whose subjectivity is the manifestation of an extreme indifference to others, determined by career aspirations. This study made possible cause reflections to understand the challenges of human emancipation and overcoming the logic of capital from the study of subjectivity production being operated in the process of production and recovery of values.